Adherence to a Dietary Approach to Stop Hypertension (DASH)-Style in Relation to Daytime Sleepiness - Pahlavani N (Dove Medical Press, 2020)
Naseh Pahlavani,1,* Sayyed Saeid Khayyatzadeh,2,3,* Vahideh Banazadeh,1 Mohammad Bagherniya,4 Maryam Tayefi,5 Saeid Eslami,6 Gordon A Ferns,7 Majid Ghayour-Mobarhan8,9 1Student Research Committee, Mashhad University of Medical Sciences, Mashhad, Iran; 2Nutrition and Food Security Research Center, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 3Department of Nutrition, Faculty of Health, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 4Department of Community Nutrition, School of Nutrition and Food Science, Food Security Research Center, Isfahan University of Medical Sciences, Isfahan, Iran; 5Department of Cardiovascular, Imam Reza Hospital, Mashhad University of Medical Science (MUMS), Mashhad, Iran; 6Department of Medical Informatics, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 7Division of Medical Education, Brighton and Sussex Medical School, Brighton, Sussex, BN1 9PH, UK; 8Department of Modern Sciences and Technologies, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 9Metabolic Syndrome Research Center, School of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran*These authors contributed equally to this workCorrespondence: Majid Ghayour-Mobarhan Tel +985138002288Fax +985138002287Email ghayourm@mums.ac.irBackground: The beneficial impact of adherence to a DASH diet on several metabolic conditions and psychological well-being has been shown previously. Dietary modification can affect sleep quality. Thus, the aim of this present study was to investigate the correlation between adherence to the DASH diet and daytime sleepiness score in adolescent girls.Methods: A total of 535 adolescent girls aged between 12 and 18 years old were recruited from different regions of Khorasan Razavi in northeastern of Iran, using a random cluster sampling method. DASH scores were determined according to the method of Fung et al. A Persian translation of the Epworth Sleepiness Scale (ESS-IR) was used to assess of daytime sleepiness. To investigate the correlation between DASH-style diet and daytime sleepiness score, we applied logistic regression analysis in crude and adjusted models.Results: As may be expected, participants with the greatest adherence to the DASH diet had significantly higher intakes of fruits, vegetables, low-fat dairy products, fish and nuts, and lower consumption of refined grains, red and processed meat, sugar-sweetened beverages and sweets. There was an inverse correlation between adherence to the DASH-style diet and scores for daytime sleepiness in crude model (β= − 0.12; P=0.005). These findings were remained significant after adjustment for confounding variables (β= − 0.08 P=0.04).Conclusion: There is an inverse correlation between adherence to DASH diet and daytime sleepiness score. Further studies, particularly longitudinal studies, are required to determine whether dietary intervention may improve daytime sleepiness.Keywords: DASH diet, sleep, adolescents, daytime functioning